GST: Impact on Indian Economy: Analyzing the Impact of GST on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
GST is a single national uniform tax levied across India on all goods and services. In GST, all Indirect taxes such as excise duty, central sales tax (CST) and value- added tax (VAT) etc. will be subsumed under a single regime. Introduction of The Goods and Services Tax (GST) expected as a significant step towards a comprehensive indirect tax reform in the country, which would lead India for its economic growth. The Proposed study is designed to know the impact of GST on Indian Economy with the help of its individual effect on different sectors. The Study is Exploratory in nature and secondary data has been used for the study. The data will be collected from different Journals, Periodicals. Newspapers and Internets.